Ab initio study of ceria films for resistive switching memory applications. (3rd October 2017) - Firdos, Mehreen; Hussain, Fayyaz; Imran, Muhammad; Ismail, Muhammad; Rana, A M; Arshad Javid, M; Majid, Abdul; Arif Khalil, R M; Ullah, Hafeez
Abstract: The aim of this study is to investigate the charge distribution/relocation activities in relation to resistive switching (RS) memory behavior in the metal/insulator/metal (MIM) structure of Zr/CeO2 /Pt hybrid layers. The Zr layer is truly expected to act not only as an oxygen ion extraction layer but also as an ion barrier by forming a ZrO2 interfacial layer. Such behavior of the Zr not only introduces a high concentration of oxygen vacancies to the active CeO2 layer but also enhances the resistance change capability. Such Zr contributions have been explored by determining the work function, charge distribution and electronic properties with the help of density functional theory (DFT) based on the generalized gradient approximation (GGA). In doped CeO2, the dopant (Zr) plays a significant role in the formation of defect states, such as oxygen vacancies, which are necessary for generating conducting filaments. The total density of state (DOS) analyses reveal that the existence of impurity states in the hybrid system considerably upgrade the performance of charge transfer/accumulation, consequently leading to enhanced RS behavior, as noticed in our earlier experimental results on Zr/CeO2 /Pt devices. Hence it can be concluded that the present DFT studies can be implemented on CeO2 -based RRAM devices, which have skyscraping potential for future nonvolatile memory (NVM) applications.